Do women gain or lose from becoming mothers? A comparative wage analysis in 20 European countries - O'Dorchai, Sîle (Brussels, 2009)
"This paper analyses disparity in women’s pay across 20 European countries using EU-SILC 2006. First, a selectivity-adjusted gender pay gap is computed and examined in each of the countries. Next, the impact of parenthood is analysed. We show that women suffer a wage disadvantage compared with men all over Europe. Motherhood usually reinforces the gender gap but discrimination is more sex- than maternity-related so that it concerns all women as (potential) mothers. Fatherhood has a positive impact on men’s wages. Finally, in most countries, the wage gap between mothers and fathers is even deeper than that between women and men."